(3TWH GdYdGeI GdJLGQjI aj VhA GLJgGO eMceI GdYOd GdYdjG (B/s - (3YSGa, TPi CMeOs ((3YeGf(B: s (3OGQ GdKbGaI ddfTQ hGdJhRjY(B, s, 2011)
(3GdebOeI(B-(3GdaUd GdChd (B: (3CSHGH TWH GdYdGeI GdJLGQjI GdeSLdI (B: (3GdeHMK GdChd (B: (3TWH GdYdGeI GdJLGQjI GdeSLdI deNGdaI TQhW GdJSLjd (B: (3GdeWdH GdChd (B: (3TWH GdYdGeI GdJLGQjI GdeSLdI deNGdaI ELQGAGJ GdJSLjd (B: (3GdeWdH GdKGfj (B: (3TWH GdYdGeI GdJLGQjI GdeSLdI deNGdaI GdTQhW GdehVhYjI (B: (3GdeHMK GdKGfj (B: (3TWH GdYdGeI GdJLGQjI GdeSLdI dCSHGH eJYdbI HeGdcgG (B: (3GdeWdH GdChd (B: (3TWH GdYdGeI GdJLGQjI GdeSLdI HSHH YOe GdGSJYeGd (B: (3GdeWdH GdKGfj (B: (3TWH GdYdGeI GdJLGQjI GdeSLdI HSHH YOe GdJLOjO hHfGA Ydi WdH eGdcgG(B-(3GdaUd GdKGfj (B: (3ELQGAGJ TWH GdYdGeI GdJLGQjI GdeSLdI hBKGQgG (B: (3GdeHMK GdChd (B: (3ELQGAGJ TWH GdYdGeI GdJLGQjI GdeSLdI (B: (3GdeWdH GdChd (B: (3ELQGAGJ TWH GdYdGeI GdJLGQjI deNGdaJgG TQhW GdJSLjd GdTcdjI hGdehVhYjI (B: (3GdeWdH GdKGfj (B: (3ELQGAGJ TWH GdYdGeI GdJLGQjI dCSHGH eJYdbI HeGdcgG (B: (3GdeHMK GdKGfj (B: (3BKGQ TWH GdYdGeI GdJLGQjI GdeSLdI (B: (3GdeWdH GdChd (B: (3CKQ TWH GdYdGeI GdeSLdI Ydi edcjJgG hGdJUQaGJ GdhGQOI YdjgG (B: (3GdeWdH GdKGfj (B: (3CKQ TWH GdYdGeI GdeSLdI Ydi MeGjJgG GdbGfhfjIs
(3HHdjhZQGajG(B: (3U(B.293-301s
Keywords: (3GdJLGQIs; (3GdYdGeGJ GdJLGQjIs; (3GdbGfhf GdJLGQjs